Hydrogen: A Novel Treatment Strategy in Kidney Disease - Bo Wang; Zhuoshu Li; Longfei Mao; Mingyi Zhao; Bingchang Yang; Xiaowu Tao; Yuxiang Li; Guangming Yin (Karger Publishers, 2022)
Background: Hydrogen is a chemical substance that has yet to be widely used in medicine. However, recent evidence indicates that hydrogen has multi-faceted pharmacological effects such as antioxidant, anti-inflammatory, and antiapoptotic properties. An increased number of studies are being conducted on the application of hydrogen in various diseases, especially those affecting the renal system. Summary: Hydrogen can be inhaled, as a gas or liquid, and can be administered orally, intravenously, or locally. Hydrogen can rapidly enter suborganelles such as mitochondria and nucleus by simple diffusion, producing reactive oxygen species (ROS) and triggering DNA damage. Hydrogen can selectively scavenge hydroxyl radical (•OH) and peroxynitrite (ONOO−), but not other reactive oxygen radicals with physiological functions, such as peroxyanion (O2−) and hydrogen peroxide (H2O2). Although the regulatory effect of hydrogen on the signal transduction pathway has been confirmed, the specific mechanism of its influence on signal molecules remains unknown. Although many studies have investigated the therapeutic and preventive effects of H2 in cellular and animal experiments, clinical trials are few and still far behind. As a result, more clinical trials are required to investigate the role of hydrogen in kidney disease, as well as the effect of its dose, timing, and form on the overall efficacy. Large-scale randomized controlled clinical trials will be required before hydrogen can be used to treat renal illnesses. Key Messages: This article reviews the mechanisms of hydrogen in the treatment of renal disease and explores the possibilities of its use in clinical practice.